2002
DOI: 10.1046/j.1365-2028.2002.00378.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photoperiod on the reproductive condition of Nile grass rats (Arvicanthis niloticus) from an equatorial population

Abstract: We evaluated the e¡ects of photoperiod on the reproductive condition of male and female Nile grass rats (Arvicanthis niloticus) descended from members of an equatorial population trapped 28S of the equator. Study animals housed in 12:12 light:dark (LD) cycles were transferred either to short photoperiod (9:15) or long photoperiod (15:9) for 9 weeks (males) or 11weeks (females), and various reproductive parameters were assessed. We observed no di¡erences between shortand long-day males with respect to plasma co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…In contrast, day length did not affect either testes size or spermatogenesis in both S. campestris and R. pumilio, both of which seem to breed opportunistically in southern Africa (Bernard & Hall, 1995;Jackson & Bernard, 1999. In addition, Nunes et al (2002) found that photoperiod does not influence plasma testosterone concentration, testes size and seminal vesicle mass in males of the seasonally breeding Nile grass rat (Arvicanthis niloticus) from an equatorial population. Other rodents, bats and shrews, which occur near the equator, have also been found to be non-responsive to photoperiod (Rissman et al, 1987;Heideman & Bronson, 1990;O'Brien, Curlewis & Martin, 1993).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In contrast, day length did not affect either testes size or spermatogenesis in both S. campestris and R. pumilio, both of which seem to breed opportunistically in southern Africa (Bernard & Hall, 1995;Jackson & Bernard, 1999. In addition, Nunes et al (2002) found that photoperiod does not influence plasma testosterone concentration, testes size and seminal vesicle mass in males of the seasonally breeding Nile grass rat (Arvicanthis niloticus) from an equatorial population. Other rodents, bats and shrews, which occur near the equator, have also been found to be non-responsive to photoperiod (Rissman et al, 1987;Heideman & Bronson, 1990;O'Brien, Curlewis & Martin, 1993).…”
Section: Discussionmentioning
confidence: 73%
“…In addition, Nunes et al . () found that photoperiod does not influence plasma testosterone concentration, testes size and seminal vesicle mass in males of the seasonally breeding Nile grass rat ( Arvicanthis niloticus ) from an equatorial population. Other rodents, bats and shrews, which occur near the equator, have also been found to be non‐responsive to photoperiod (Rissman et al ., ; Heideman & Bronson, ; O'Brien, Curlewis & Martin, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, species that inhabit tropical climates have expanded breeding seasons compared to closely related species that live in temperate climates. Several studies have observed that short days do not inhibit reproduction in tropical rodents (Demas and Nelson, 1998;Heideman and Bronson, 1990;Nunes et al, 2002), although this outcome does not necessarily reflect an inability to detect slight changes in photoperiod in these species (Hau et al, 1998). In the tropics, photoperiod may be a less informative predictor of impending climate, so other cues may be more useful for timing reproductive activity.…”
Section: Introductionmentioning
confidence: 99%
“…where seasonal changes in day length can be perceived by this species). However, the recent study by Nunes et al. (2002) revealed that photoperiod experiments were unable to induce any reproductive changes among A. niloticus individuals from populations whose native habitat is located further south in Kenya (near 2° S latitude); suggesting that intra‐specific variation for this trait may be present within A. niloticus .…”
Section: Latitudinal Changes In Habitat Distribution Of a Niloticus mentioning
confidence: 97%